1985
DOI: 10.1044/jshd.5004.335
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Children's Knowledge of Sociolinguistic Rules for Speech Therapy Lessons

Abstract: Eight dyads of misarticulating school children (M = 7:9 years) enrolled in clinical programs were videotaped while they role-played 5-min remedial articulation lessons. Analysis of lesson transcripts was carried out at selected levels (lesson management, roles, discourse contexts, communicative acts, discourse sequences, and topic introduction). The "clinicians" controlled the lesson tasks and topics and used communicative acts in a manner typical of adult clinicians. The "clients" role-played cooperatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…To most effectively structure a language learning environment, we need to view intervention not only from an observer's vantage point and a clinician's participant view, but also from the child's perspective (Ripich & Panagos, 1985).…”
Section: Children's Perception Of Roles In Intervention Danielle N Rmentioning
confidence: 99%
“…To most effectively structure a language learning environment, we need to view intervention not only from an observer's vantage point and a clinician's participant view, but also from the child's perspective (Ripich & Panagos, 1985).…”
Section: Children's Perception Of Roles In Intervention Danielle N Rmentioning
confidence: 99%
“…Becker and Silverstein, 1978;Prutting, Bagshaw, Goldstein, Juskowitz and Umen, 1978;Letts, 1985;Ripich and Panagos, 1985;Panagos, Bobkoff and Scott, 1986). These works have provided descriptions of what happens in and who speaks about what in therapy, thus providing insights about language and an impetus for further research.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Crystal (1981Crystal ( , 1982 noted that prosody in clinical environments is unlike normal adult-directed speech AND unlike typical child-directed speech (CDS), and Panagos, et al (1986) labelled the prosodic characteristics of clinical discourse as being 'finer' in tone, louder, and slower than those found in nonclinical contexts, which they described as fast and lively. Additionally, Ripich and Panagos (1985) described instances in which children role-playing SLPs ('clinicians') modified prosody. Such 'clinicians' reportedly used slow rates, increased pitch variations, increased pitch levels, and increased loudness.…”
Section: Introductionmentioning
confidence: 99%
“…We begin by assuming that the clinician's presuppositions about therapy are established through varied sociolinguistic experiences, producing refined intuition for the structures and forms of 'therapy talk' as dictated by the formalities of the setting and the role of speech therapist (Ripich, 1982;Ripich and Panagos, 1985). The presentation of material is descriptive: nonverbal elements are illustrated with descriptive statements derived from clinical observation, and with excerpts from transcribed videotaped lessons conducted by working clinicians (Bobkoff, 1982;Kovarsky, in press).'…”
Section: Introductionmentioning
confidence: 99%
“…Ripich (1982;Ripich and Panagos, 1985) reported that children enrolled in school therapy asked to role-play therapist and client were able to do so with great accuracy and facility. The children could mimic nonverbal behaviours quite perfectly.…”
mentioning
confidence: 98%